Exploring EFL Teachers’ Strategies in Teaching Vocabulary at Senior High School Level (Case Study at SMKN 1 Barru) - Farahdiba, Aulya; Sunra, La; Amirullah, Amirullah (State University of Makassar, 2024)
The objectives of the research were to find out (1) the EFL teachers’ strategies in teaching English at Senior High School level; (2) the EFL teachers’ strategies in teaching vocabulary at Senior High School level; and (3) the EFL teachers’ problem in teaching vocabulary at Senior High School level. This research applied qualitative method. The subject of this study was an English teacher who taught at SMKN 1 Barru. The data collected were observation, questionnaire checklist and interview. The result of this study showed that (1) the EFL teacher uses five strategies in teaching English, discussion and demonstration strategies, using electronic media as a learning media, using games(applications), teaching vocabulary strategy; (2) the EFL teacher uses four strategies in teaching vocabulary to students, such as learning new vocabulary strategies independently without the help of teachers and other students, using strategies that involve teachers and other students, using strategies to remember new words or vocabulary, using games (applications); (3) the several problems faced by the teacher in teaching vocabulary, such as lack of motivation, phone dependency and self-confidence. Keywords: Teaching Strategies, Vocabulary, Teaching Vocabulary.